Rhinovirus-induced first wheezing episode predicts atopic but not nonatopic asthma at school age - Lukkarinen, Minna (J Allergy Clin Immunol, 2017)
BACKGROUND: Persistent childhood asthma is mainly atopy driven. However, limited data exist on the risk factors for childhood asthma phenotypes. OBJECTIVE: We sought to identify risk factors at the first severe wheezing episode for current asthma 7 years later and separately for atopic and nonatopic asthma. METHODS: One hundred twenty-seven steroid-naive children with the first severe wheezing episode (90% hospitalized/10% emergency department treated) were followed for 7 years. The primary outcome was current asthma at age 8 years, which was also analyzed separately as atopic and nonatopic asthma. Risk factors, including sensitization, viral cause, and other main asthma risk factors, were analyzed. RESULTS: At study entry, median age was 11 months (interquartile range, 6-16 months); 17% were sensitized, and 98% were virus positive. Current asthma (n = 37) at 8 years was divided into atopic (n = 19) and nonatopic (n = 18) asthma. The risk factors for current atopic asthma at study entry were sensitization (adjusted odds ratio [OR], 12; P < .001), eczema (adjusted OR, 4.8; P = .014), and wheezing with rhinovirus (adjusted OR, 5.0; P = .035). The risk factors for nonatopic asthma were the first severe respiratory syncytial virus/rhinovirus–negative wheezing episode (adjusted OR, 8.0; P = .001), first wheezing episode at age less than 12 months (adjusted OR, 7.3; P = .007), and parental smoking (adjusted OR, 3.8; P = .028). CONCLUSIONS: The data suggest diverse asthma phenotypes and mechanisms that can be predicted by using simple clinical markers at the time of the first severe wheezing episode. These findings are important for designing early intervention strategies for secondary prevention of asthma.